Gender Role in Teak Plantation at Paklay District Sayaboury Province, Lao PDR: https://doi.org/10.69692/SUJMRD09073 - SITTHIVONG1, KiPhet; PHONETIP, Khamtan; LING, Stuart; BOUPHA, Latsamy; CHAISEE, Somleuthai (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This paper investigates the gender role in teak (Tectona grandis) plantation in Paklay District, Xayaboury Province. There are two objectives of study: 1) to analyze the state of gender equality in plantation activities, and 2) to analyze the satisfaction of men and women in undertaking their plantation responsibilities. This research gathered data from 124 families in the three villages, which corresponded to 100% of those growing teak. The household interview gathered both quantitative and qualitative data using the data management program KOBO toolbox. The results of showed that men and women participate equally in nine of 12 plantation activities (or 75%) being land clearing, soil preparation, planting lines, planting, tree maintenance, pruning-thinning, building a fire break, weeding and marketing (selling). In terms of satisfaction, women expressed themselves to be ‘very satisfied’ on a Likurt scale, whereas men were only ‘satisfied’. It was found that men and women discussed the work required in the teak plantation together and divided their responsibilities in accordance with whether the work was perceived to be light or heavy and with bodily strength of those in the household. The gender equality and mutual respect between the sexes from this cooperation meant that both men and women were satisfied.